A conjecture on product decompositions in simple groups - Liebeck, M; Nikolov, N; Shalev, A (2010)
We propose a conjecture concerning decompositions of finite simple groups as products of conjugate subgroups, and prove it for a large class of maximal subgroups. © European Mathematical Society.